A Beauvoirian Feminist Analysis of Women’s Representation in William Faulkner’s “A Rose for Emily” - Nafdi Irawan; Afriana Afriana (Asosiasi Ide Bahasa Kepri, 2025)
This study analyzes the representation of women in William Faulkner’s A Rose for Emily through Simone de Beauvoir’s feminist theoretical framework. Employing Beauvoir’s concepts of the Other, myths of woman, and women’s categorization as prostitute, the research examines women's representation reflected in the narrative that frames the story of Faulkner's A Rose for Emily, and unveils the perspective of Faulkner as the male author on women as implied in the story. The data are collected through the primary source involved close reading of Faulkner's